Rare species of crustaceans of natural protected areas of the Kharkiv region - Sidorovsky, S.; Kryshtal, E. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
The results of the study of rare and endangered species of crustaceans in the natural protected areas in the Kharkiv, Zmiyiv, Krasnokutsk and Dvorichna districts of the Kharkiv Region are presented for 2010–2016. In general, 13 rare species were found, including five species – Hemidiaptomus rylowi Charin, 1929, Branchipus schaefferi (Fischer, 1834), Tanymastix stagnalis Linnaeus, 1758, Drepanosurus birostratus (Fischer, 1851) and Gmelina pusilla (Sars, 1896), which are included in the Red List of Ukraine and eight species – Eudiaptomus transylvanicus (Daday, 1890), Lynceus brachyurus Müller, 1776, Cyzicus tetracerus (Krynicki, 1830), Streptocephalus torvicornis (Waga, 1842), Chirocephalus shadini (Smirnov, 1928), Chirocephalus josephinae (Grube, 1853), Lepidurus apus (Linnaeus 1758) and Triops cancriformis (Bosc, 1803), included in the Red List of the Kharkiv region. This represents 13% of the crustacean fauna of the region except ostracods. The geographical distribution of rare and endangered species of crustaceans was revised for the national natural parks Gomilshanski lisy, Dvorichanskyi and Slobozhanskyi, Velykyi Burluk Steppe Regional Landscape Park, the Kharkiv Zoo and Kryukiv Reserve. About 31% of rare species were found only in unprotected areas.